TANGGUNG JAWAB PELAKU PIDANA PELANGGARAN DALAM PERSPEKTIF RESTORATIVE JUSTICE - Karim Karim (Universitas Airlangga, 2017)
The handling of the minor criminal act case settlement tends to be conducted as a general crimanal act because it is only focused on criminal responsibility of perpetrators which is based on the responsibility of their actions and faults, without considering the quality orvalues of the crime objects, so it breaks the sense of justice in society. Whereas, basically a minor criminal act is a simple and harmless criminal act, and it just cause merely little losses of the victims. For this reason, an alternative case settlement of the minor criminal act is needed by restorative justice approach which has a more emphasis on the creation of conditions of fairness and balance between the perpetrator to the victim. Because the current criminal justice procedure focuses solely on criminal prosecution and ignores the interests of the victim, thus it is transformed into a process of dialogue / mediation, involving the victim to create a fairer and more balanced minor criminal act case settlement.The criteria for completing the criminal cases through restorative justice is that the perpetrator is not punished .In other words through this restorative models, perpetrator does not need to go to jail if the interests of the victim and the loss have been restored or have been recovered, the victim and the community have forgiven, while the perpetrator has expressed regret.